Maternal Role and Gender Integration in Preventing Stunting among Children - Rr. Rina Antasari; Dolla Sobari; Elhefni Elhefni; Nilawati Nilawati; RA. Hoetary Tirta Amalia (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Child stunting remains a serious public health issue in Indonesia, with a high prevalence despite various intervention programs. This study aims to analyze the relationship between a mother’s age at marriage, her knowledge about stunting, and her gender role in preventing stunting. Methods: This research employed a descriptive analytical design with cross-sectional method and quota sampling technique. A total of 60 children aged 2–5 years in Palembang were divided into two groups: stunted and non-stunted children. Data were collected through questionnaires, interviews, and observations, then analyzed using chi-square tests, Independent Sample T-Test, and Mann Whitney tests with SPSS. Results: The results show a significant relationship between mothers marrying before the age of 20 and the risk of delivering low birth weight babies, which contributes to stunting. Limited maternal knowledge about stunting also increases the likelihood of stunting cases. From a gender perspective, mothers of stunted children tend to have limited access, participation, control, and benefits in family decision-making. Conclusion: In conclusion, mothers play a crucial role in stunting prevention; however, support from husbands and government policies to enhance maternal knowledge and promote gender equality within households are also essential to reduce stunting rates effectively.